Decision-making on shared sanitation in the informal settlements of Kisumu, Kenya. Issue 5 (3rd September 2017) - Simiyu, Sheillah; Swilling, Mark; Cairncross, Sandy
Abstract: Unlike most quantitative studies that investigate decision-making on investing in sanitation, this study adopted a qualitative approach to investigate decision-making on shared sanitation in the informal settlements of Kisumu city, in Kenya. Using a grounded theory approach, landlords and tenants were interviewed to identify sanitation decisions, individuals involved in decision-making and factors influencing decision-making. The results indicate that the main sanitation decisions are on investment, emptying, repair and cleaning. Landlords make investment, emptying and repair decisions, while tenants make cleaning decisions. Absentee landlords are less involved in most decision-making compared to live-in landlords, who rarely consult tenants in decision-making. Tenants make decisions after consultations with a third party and often collectively with other tenants. Sanitation interventions in informal settlements should thus, target landlords and tenants, with investment efforts being directed at landlords and maintenance efforts at tenants.